URGENSI PENANAMAN NILAI-NILAI BUDAYA BERBASIS TRADISI SAPRAHAN DALAM PEMBELAJARAN SEJARAH LOKAL DI KOTA PONTIANAK - Emusti Rivasintha Marjito; Karel Juniardi (SWADESI: Jurnal Pendidikan dan Ilmu Sejarah, 2021)
This study entitled Urgency in Cultivating Cultural Values Based on Saprahan Traditions in Learning History in Pontianak City. This study aims to find out the tradition of saprahan in Pontianak City, cultural values in the tradition of the saprahan in Pontianak City, and the cultivation of cultural values based on the saprahan in learning local history in the city of Pontianak. This study uses the literature or literature method by reviewing books, journals, and other written sources related to the research theme. The results of the study recommend that the saprahan tradition is very important to be preserved in Pontianak City because it contains cultural values such as religious values, togetherness, hospitality, and brotherhood; cultural values in the saprahan tradition in Pontianak City can be implemented in learning local history; and the cultivation of cultural values based on the saprahan in learning local history in Pontianak City can be done through contextual learning.